Social Media Platform Preferences for Enhancing English Language Skills: A Study of Secondary School and University Students in Selangor - Damio, Siti Maftuhah; Patrick, Marion Clarice Tari; Iswahyuni (EDUCATUM Journal of Social Sciences, 2024)
The impact of technological advancements, specifically social media, on the enhancement of English language proficiency has garnered mixed responses from individuals, despite the limitations of conventional learning materials in this regard. This study focused on assessing the English language skills of secondary school and university students, revealing positive outcomes. Employing a quantitative approach through the distribution of questionnaires which include objective and subjective questions among students in Selangor, it was observed that both groups favoured YouTube as their preferred platform for language improvement, while Facebook was rated the least favoured by both categories. Regarding the disparities in social media platform preferences and their effects on students’ English language skills, the research found no significant differences. This research also aims to highlight the potential of social media platforms in effectively enhancing students’ English language skills, and it is hoped that both educators and students can tap into this resource to their advantage.